Choroidal Vascularity Index (CVI)--A Novel Optical Coherence Tomography Parameter for Monitoring Patients with Panuveitis? - Rupesh Agrawal; Mohammed Salman; Kara-Anne Tan; Michael Karampelas; Dawn A Sim; Pearse A Keane; Carlos Pavesio (PLoS ONE)
Purpose To compute choroidal vascularity index (CVI) using an image binarization tool on enhanced depth imaging (EDI)-optical coherence tomography (OCT) scans as a non-invasive optical tool to monitor progression in panuveitis and to investigate the utility of volumetric data from EDI-OCT scans using custom image analysis software. Materials and methods In this retrospective cohort study, segmented EDI-OCT scans of both eyes in 19 patients with panuveitis were taken at baseline and at 3-month follow-up and were compared with EDI-OCT scans of normal eyes. Subfoveal choroidal area was segmented into luminal (LA) and stromal interstitial area (SA). Choroidal vascularity index (CVI) was defined as the proportion of LA to the total circumscribed subfoveal choroidal area (TCA). Results The mean choroidal thickness was 265.5±100.1μm at baseline and 278.4±102.6μm at 3 months follow up (p = 0.06). There was no statistically significant difference in TCA between study and control eyes (p = 0.08). CVI in the control group was 66.9±1.5% at baseline and 66.4±1.5% at follow up. CVI was 74.1±4.7% at baseline and 69.4±4.8% at 3 months follow up for uveitic eyes (p<0.001). The % change in CVI was 6.2 ±3.8 (4.3 to 8.0) for uveitic eyes, which was significantly higher from % change in CVI for control eyes (0.7±1.1, 0.2 to 1.3, p<0.001). Conclusion The study reports composite OCT-derived parameters and CVI as a possible novel tool in monitoring progression in panuveitis. CVI may be further validated in larger studies as a novel optical tool to quantify choroidal vascular status.